Online resources on gene networks containing human and animal data - E. V. Ignatieva; D. A. Afonnikov; N. A. Kolchanov (Вавиловский журнал генетики и селекции, 2018)
Gene networks are molecular genetic systems that ensure the formation of phenotypic characteristics of organisms (molecular, biochemical, structural, morphological, behavioral, etc.) based on  information encoded in their genomes. Reconstruction of gene networks provides a methodological basis for modern systems biology. In this regard, the information on the structural and functional organization of gene networks accumulated in modern databases is extremely valuable. This review characterizes a number of Internetaccessible information resources oriented to humans and animals and containing data on gene networks and their functional modules. Without pretending to fully cover all information resources containing data related to humans and animals on the subject, the current review was created to report the current status of the problem and to present the criteria according to which we propose to evaluate the utility of webresources for specific research tasks. On this basis, we compiled and characterized a collection of databases containing information on metabolic and signaling pathways, as well as pathways of regulation of biological processes at the cellular and organismal levels. In addition, we observed the characteristics of several wellknown databases containing data on interactions between biomolecules of various types. The following characteristics of databases were considered: (1) the types of information accumulated in the databases; (2) methods of data presentation; (3) methods of data collection; (4) data sources; (5) special search tools and options for data analysis. A comparison of the above characteristics showed that the databases are very heterogeneous according to their scopes, sources and types of data, interfaces, as well as according to their search options and data analysis tools. It was concluded that at the first step of the gene network reconstruction it is important to form a full set of information resources from which the data can be obtained. The web portals accumulating information about the databases that may be useful for the reconstruction and analysis of gene networks are specified.